Mocap-based aiming point trajectory assessment in shooting and the effect of marker dimensions - Yilmaz, V.; Amca, A. M. (International Journal of Sports Science & Coaching, 2025)
The aiming point is the most crucial criterion for a successful shot in all shooting events. This study investigated the motion-capture (Mocap) based aiming point assessment method in three steps: the static fluctuations of the markers in four dimensions were observed; the aiming point results of the Mocap-based method were compared with laser trace on the target in static and dynamic conditions; the effects of marker dimensions on the aiming point trajectories were examined. A wooden lath, with two sets of reflective markers in four dimensions (12-18 mm) and a laser, was fixed on a tripod and aimed at the center of the target. The lath was left stationary and then moved twenty times as in shooting. While a camera followed the laser trace on the target, the Mocap system followed the markers, and aiming point data were calculated. Compared to larger markers, significantly smaller errors in static marker fluctuations were found for the 12 mm marker (p < 0.008). Aiming point trajectory length in static conditions showed significant differences between marker pairs and laser. No significant differences between the laser and the marker pairs of 12, 14, and 16 mm were noticed in dynamic conditions. The Bland-Altman analysis showed that the 12 mm marker pair had the smallest bias and a strong agreement with the laser-based method.